Analisis Percepatan Waktu Menggunakan Metode Time Cost Trade Off (TCTO) Pada Proyek Preservasi Jalan (Studi Kasus: Preservasi Jalan Ruas Biluhu Barat – Gorontalo) - Winarsi Junizar Paputungan; Arfan Usman Sumaga; Moh. Yusuf Tuloli (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This research aimed to analyze the acceleration of project execution time using the Time Cost Trade Off (TCTO) method on the road preservation project of the Biluhu Barat – Gorontalo segment. Delays in construction projects may result in negative impacts on time, cost, and work quality. Therefore, acceleration strategies are required to reduce project duration without compromising cost efficiency. The TCTO method was applied through simulations involving overtime work and the addition of heavy equipment for activities located on the critical path. The data analyzed in this research included the time schedule, Budget Plan (RAB), and Unit Price Analysis (AHSP). Simulations were conducted on 7 critical path work items using Microsoft Project 2021 software. The analysis results indicate that applying the Time Cost Trade Off method with additional overtime hours led to both time and cost efficiency. The project cost under the 1-hour overtime alternative was recorded at IDR 42,011,519,325.19 with a duration of 146 days; for 2-hour overtime, the cost was IDR 42,190,670,502.55 with a duration of 142 days; for 3-hour overtime, the cost reached IDR 42,389,837,881.99 with a duration of 140 days; and for 4-hour overtime, the total cost was IDR 42,624,339,782.86 with a duration of 138 days.